Web-Based Academic Information Systems in Vocational School - Lengkong , Jeffry Sony Junus; Jacobus, Susan N H; Dondokambey, Robby; Ratumbuisang, Keith F.; Paath, Deicy; Liow, Evans S. (International Journal of Information Technology and Education, 2023)
An academic information system is an application that can facilitate to processing of data and information related to academic problems. Currently, SMK Negeri 1 Tondano as one of the vocational schools in North Sulawesi still uses manual methods in processing the data and information needs, so it feels less effective and efficient. This causes the data process to not be integrated properly, and it takes a long time to process data or information. This research was conducted to develop a web-based academic information system at SMK Negeri 1 Tondano. Where this information system is expected to be able to help the data and information processing process. In developing the system to be built, the research method used is the prototype development method and Unified Modeling Language (UML) modeling to simplify the design of the system to be built. Based on the results of system testing using black-box testing, it is stated that the system can run as well as expected.